Successful delivery after in vitro fertilization-embryo transfer in a woman with metachronous primary cancer of ovary and endometrium: a case report - Yichang Tian; Yu Liang; Xiaokui Yang (BMC, 2023)
Abstract Background The appearance of malignancies at various times in the same individual, excluding metastases of the initial primary cancer, is termed multiple primary cancers. Double primary gynecological cancers cause inevitable damage to female reproductive function, and the preservation of fertility in such patients remains a challenging issue as relatively few cases have been reported. This case report provides management options for dual primary ovarian and endometrial cancers, including the choice of ovulation induction protocols, considerations during pregnancy and parturition, with the aim of providing assistance to clinicians. Case presentation We report a case of a 39-year-old woman with primary infertility and a medical history of right-sided ovarian mucinous borderline tumor with intraepithelial carcinoma, left-sided ovarian mucinous cystadenoma and endometrial cancer, who successfully conceived with in vitro fertilization-embryo transfer (IVF-ET) after three different ovulation induction protocols. During her pregnancy, she was complicated by central placenta praevia with placental implantation and eventually delivered a healthy female infant by caesarean section at 33 gestational weeks. Conclusions For patients with double primary gynecological cancers who have an intense desire for fertility, the most appropriate oncological treatment should be applied according to the patient's individual situation, and fertility preservation should be performed promptly. Ovulation induction protocol should be individualized and deliberate, with the aim of ensuring that the patient's hormone levels do not precipitate a recurrence of the primary disease during induction of ovulation and maximizing fertility outcomes. In addition, the risk of postpartum hemorrhage due to placental factors cannot be neglected in such patients.